KAJIAN EMPIRIS ATAS PERILAKU BELAJAR, KECERDASAN EMOSIONAL, EFIKASI DIRI TERHADAP STRES KULIAH MAHASISWA AKUNTANSI PADA UNIVERSITAS DI DAERAH ISTIMEWA YOGYAKARTA - Toni Nur Wijanarko; Kurniawan Ali Fachrudin (Jurnal REKSA: Rekayasa Keuangan, Syariah dan Audit, 2014)
Learning behavior, emotional intelligence and self-efficacy is a trait that is on the individual in achieving success. This research study repair Marita et al (2007), in his research stated behavioral variables affect learning and emotional intelligence to the stress of college. This study adds efficacy variables influencing stress in college. This research was conducted with the aim of analyzing whether there is influence learning behavior, emotional intelligence and self-efficacy accounting students against college stress. This study is a survey research on accounting students in Yogyakarta Special Region. The population in this study were students in accounting at the University of DIY and using convenience sampling sample criteria. In this study, using a sample of 294 students. Analysis of the indigenous is used factor analysis, multiple regression, F-test and t-test. The results showed behavioral variables studied, emotional intelligence and selfefficacy variables affect the college stress.